Nomenclatural Notes on a Caecilian (Amphibia : Gymnophiona) Name - Das, Indraneil (Society for the Study of Amphibians and Reptiles, 2006)
Bhatta and Srinivasa (2004) described a new species of caecilian, which they named Gegeneophis madhavai, from “Doddinaguli locality (Mudur Village, Kundapura Taluk, Udupi District, Karnataka State”…. “situated adjacent to the Mookambika Wildlife Sanctuary in the Western Ghats” (in southwestern India). The new species was named for four individuals who share a first name, namely, Madhava Bhat, Madhavarao Bhide, Madhava Anantha and Madhava Gadgil. The spelling of the first (= given) name of the last individual is, in fact, Madhav, a contemporary north Indian version of the spelling. The name is derived from the Sanskrit, meaning vernal, originating from the name Madhu, a legendary king, whose most famous descendant is Krishna, a Hindu god (see Hanks and Hodges 1990).